Long‐lasting efficacy and safety of lenalidomide maintenance in patients with relapsed diffuse large B‐cell lymphoma who are not eligible for or failed autologous transplantation. Issue 3 (5th May 2020) - Ferreri, Andrés J. M.; Sassone, Marianna; Angelillo, Piera; Zaja, Francesco; Re, Alessandro; Di Rocco, Alice; Spina, Michele; Fabbri, Alberto; Stelitano, Caterina; Frezzato, Maurizio; Volpetti, Stefano; Zambello, Renato; et al.
Abstract: We report final results of a phase II trial addressing efficacy and feasibility of lenalidomide maintenance in patients with chemosensitive relapse of diffuse large B‐cell lymphoma (DLBCL) not eligible for or failed after autologous stem cell transplantation (ASCT). Patients with relapsed DLBCL who achieved at least a partial response to salvage chemoimmunotherapy were enrolled and treated with lenalidomide 25 mg/day for 21 of 28 days for 2 years or until progression or unacceptable toxicity. Primary endpoint was 1‐year PFS. Forty‐six of 48 enrolled patients were assessable. Most patients had IPI ≥2, advanced stage and extranodal disease before the salvage treatment that led to trial registration; 28 (61%) patients were older than 70 years. Lenalidomide was well tolerated. With the exception of neutropenia, grade‐4 toxicities occurred in <1% of courses. Three patients died of complications during maintenance and three died due to second cancers at 32 to 64 months. There were 13 SAEs recorded in 12 patients; all these patients but two recovered. Lenalidomide was interrupted due to toxicity in other 6 patients, and 25 patients required dose reduction (transient in 21). At 1 year from registration, 31 patients were progression free. After a median follow‐up of 65 (range 39‐124) months, 22 patients remain progression free, with a 5‐year PFS of 48% ± 7%. The duration of response to lenalidomide was longer than response to prior treatment in 30 (65%) patients. Benefit was observed both in de novo and transformed DLBCL, germinal‐center‐B‐cell and nongerminal‐center‐B‐cell subtypes. Twenty‐six patients are alive (5‐year OS 62% ± 7%). With the limitations of a nonrandomized design, these long‐term results suggest that lenalidomide maintenance might bring benefit to patients with chemosensitive relapse of DLBCL not eligible for or failed after ASCT. Lenalidomide was associated with durable disease control and was well tolerated in this elderly population. Further investigations on immunomodulatory drugs as maintenance in these high‐risk patients are warranted.